1969
DOI: 10.12669/pjms.322.9127
|View full text |Cite
|
Sign up to set email alerts
|

Mackenzie Treatment versus Mulligan SNAGs for Chronic Mechanical Low back pain

Abstract: Background and Objective:Chronic mechanical low back pain is common among different age groups and genders. Different manual therapy techniques combined with exercise therapy and electrotherapy modalities play an important role in its management. Our objective was to compare the effects of McKenzie extension exercisesprogram (EEP) versus Mulligan Sustained Natural Apophyseal Glides (SNAGs) for chronic mechanical low back pain (CMLBP).Methods:This randomized control trial (RCT) was conducted at Riphah Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 14 publications
2
32
1
1
Order By: Relevance
“…In total, 47 trials fulfilled the inclusion criteria, 21 of which were not included in the previous review (fig 1). 14 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In total, 47 trials fulfilled the inclusion criteria, 21 of which were not included in the previous review (fig 1). 14 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72…”
Section: Resultsmentioning
confidence: 99%
“…The countries in which the studies were conducted varied. Fifteen studies were conducted in the United States,14 28 29 33 34 40 41 44 45 46 49 54 66 70 72 seven in the United Kingdom,32 35 38 39 50 69 73 three each in Finland,42 52 71 Australia,36 51 67 and Italy,31 55 65 two each in Sweden,57 61 Denmark,53 56 Egypt,58 60 and India,59 64 and one each in Belgium,43 Spain,30 Switzerland,27 the Netherlands,47 Greece,48 Turkey,63 Pakistan,68 and Tunisia 37. All trials were published in English except the trial conducted in Tunisia, which was published in French.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…e glide occurs in the articular plane, and the movement is performed in loading [99]. e reports indicate that the addition of the SNAG technique to other rehabilitation methods improves the range of spinal mobility and reduces pain [100][101][102]. e literature also indicates that compared to incorrect mobilization, the SNAG technique did not bring better results in terms of mobility [99].…”
Section: The Merits Of the Issuementioning
confidence: 99%
“…Mulligan Sustained Natural Apophyseal Glides (SNAGs) as one of most important manual therapy treatments is also widely used by physiotherapists to treat this condition. A randomized control trial was conducted by Waqqar et al to determine the effects of McKenzie extension exercise versus Mulligan SNAGs for chronic mechanical low back pain (78). They indicated that McKenzie extension exercises program is clinically slightly more effective in the management of pain and disability as compared with Mulligan SNAGs, while Mulligan SNAGs are more effective in the improvement of lumbar ROM as compared with Mechanize EEP in the management of CMLBP.…”
Section: Physical Therapymentioning
confidence: 99%